Persistently elevated circulating Th22 reversely correlates with prognosis in HBV‐related acute‐on‐chronic liver failure. Issue 3 (March 2017) - Mo, Ruidong; Wang, Peng; Lai, Rongtao; Li, Fanlu; Liu, Yuhan; Jiang, Shaowen; Zhao, Gangde; Guo, Simin; Zhou, Huijuan; Lin, Lanyi; Lu, Jie; Cai, Wei; et al.
Abstract: Background and Aim: Hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) is an acute deterioration of liver function on chronic liver disease with immune disorder. Th22 cells and IL‐22 were correlated with inflammatory and autoimmune diseases. However, Th22 cells and IL‐22 in the pathogenesis of HBV‐ACLF remains to be elucidated. It was investigated the correlation between Th22 and prognosis in HBV‐ACLF. Methods: Seventy‐one HBV‐ACLF and 65 chronic hepatitis B patients were recruited. The peripheral frequencies of Th22, Th17 and Th1, or IL‐22 and IL‐17 were determined, using flow cytometry or ELISA, respectively. It was further analyzed the correlation between Th22 mediated circulating IL‐22 and survival rate of HBV‐ACLF patients. Results: It was upregulated that the peripheral frequencies of Th22/Th17 cells as well as plasma IL‐22 and IL‐17 in HBV‐ACLF patients, but the frequency of Th1 cells was decreased, compared with health controls. Elevated Th22 cells and IL‐22 were correlated with HBV‐ACLF disease severity. Elevated plasma IL‐22 level (>29.5 pg/ml) was correlated with poor survival rate of HBV‐ACLF patients at baseline, using Kaplan–Meier analysis. Conclusions: Persistently elevated circulating Th22 reversely correlates with prognosis in HBV‐ACLF. Th22 cells/IL‐22 might be served as biomarkers for evaluating the prognosis of HBV‐ACLF.